PERANCANGAN COMPANY PROFILE DAN MEDIA PROMOSI PARIWISATA PABRIK GULA CEPIRING KABUPATEN KENDAL - Ambar Fitriyanti, Dewi (Arty: Jurnal Seni Rupa, 2015)
In 2007, the Kendal government set Cepiring Sugar Factory as one of the tourism potential. In the process, Cepiring Sugar Factory as a tourist attraction is still not crowded because of the lack of media promotion. With the existence of these problems, the authors wanted to design a company profile and a media campaign to lift the Cepiring Sugar Factory become a tourist attraction that increase the public interest. The resulting work presents a picture Cepiring Sugar Factory in the form of photographs presented in a variation of the frame with a written description of the Cepiring Sugar Factory and background with a mix of various colors, dominated by green. Design work amounted to 12, with work of company profile in the form of booklets sized 14cmX20cm and video duration 16 minutes 52 seconds, while the work of the media campaign in the form of Standing Banner 160cmX60cm, vertical desk calendar 15cmX25cm, horizontal 25cmX15cm, Leaflet 3 folding 30cmX21cm and Leaflet 2 folding 15cmX22cm. In the manufacturing process the author direct observation, shooting to create a design company profile and media campaign using Phothoshop, Audacity and Ulead VideoStudio. The conclusions of this study project is the Company profile (Booklet and video) and media promotion (Standing Banner, desk calendars, leaflets) can be one of the media as the promotion process in improving tourism Cepiring Sugar Factory which provide information about Cepiring Sugar Factory both history and knowledge sugar production.